Exploration of Methods for Slope Stabilization Influence by Unsaturated Soil - Muhammad Farhan, Zolkepli; Mohd Fakhrurrazi, Ishak (Universiti Teknologi Malaysia, 2017)
This study will lead to the analysis of unsaturated soil using Bishop’s Simplified method which is one method to analyse slope stability in method of slices. In this study, the original formula for Bishop’s Simplified method of saturated soil were modified by adding the element of matric suction, together with unsaturated friction angle, which was applicable for the analysis of unsaturated soil. In this study, 0 kPa and 20 kPa of matric suctions were applied in the analysis for both methods. From the analysis, the result indicates that the factor of safety (FOS) value of Bishop’s Simplified method was 8.82 % higher than Fellenius’s method for 0 kPa suction, which means that the soil is in saturated condition. For 20 kPa of suction, the FOS of Bishop (1955) was 6.84 % higher than Fellenius (1936). It can be concluded that, the reason for the relative accuracy of the Bishop’s Simplified method is that in considering only the vertical equilibrium of any slice, there is no need to account for the horizontal components of the interslice forces.